Marcin syn Pawła z Gołocic (zm. 1448) – wikariusz katedry i notariusz kapituły gnieźnieńskiej, archidiakon i oficjał pomorski, skryptor kanonu mszalnego - Czyżak, Marta (Ecclesia. Studia z Dziejów Wielkopolski, 2018)
The article presents the person of Marcin son of Paweł of Gołocice, descendant of the minor gentry of Łęczyca. The author describes his career as notary (notary imperiali auctoritate, notary of the Gniezno consistory and chapter, surrogate of the Gniezno official and official of Pomerania) and beneficiary (parson of Borkowo, Sompolno and Staw, vicar of the Gniezno cathedral, Pomeranian archdeacon in the Włocławek chapter). On the one hand, emphasis is placed on Marcin’s personal talents which enabled him to perform various offices and functions in the service of the Gniezno college of vicars, cathedral and chapter (watchmaker, succentor of the cathedral choir, prefect of the construction of the cathedral). On the other hand, attention is drawn to the patronage of Władysław Oporowski, a Gniezno canon and bishop of Włocławek (1434-1449), thanks to whom Marcin of Gołocice, as one of three out of 106 vicars of the Gniezno cathedral, in the first half of the 15th century obtained prelature of the cathedral chapter and was nominated Pomeranian archdeacon in the Włocławek chapter. Marcin of Gołocice is also the only known vicar-scriptor, the author of the inscription of the canon of the Holy Mass with a detailed Polish gloss in a manuscript which is now property of the National Library of Poland.